A Comparative Evaluation between Lateral Flow Antigen Assay (LFA) and RT PCR - Murthy, Neetha S.; Sumana, M.N.; Tejashree, A.; Chitharagi, Vidyavathi B.; Mahale, Rashmi P.; Rao, Murubagal Raghavendra; Sowmya, G.S.; Gowda, Ranjitha Shankare; Deepashree, R.; Sujatha, S.R. (Research Perspectives of Microbiology and Biotechnology Vol. 4, 2024)
The Present study proposes to look for RT-PCR cycle threshold correlation with positive Rapid COVID-19 LFA results and the ability of LFAs to be used as a proxy, inexpensive marker of infectiousness in mass settings given the present global post-pandemic scenario. Lateral flow antigen assays (LFA) are a quick and affordable way to detect COVID-19 in healthcare settings with limited infrastructure. Rapid diagnostic tests are essential for early, timely case identification that allows for supportive care and patient isolation. In light of the COVID-19 pandemic, molecular testing is still an expensive endeavor. Moreover, residual RNA cannot be distinguished from replication-competent viruses using molecular techniques. The present study is a retrospective cross-sectional hospital-based study of 1.25 years duration (September 2020- January 2022). Rapid COVID-19 LFA results were compared with Real-time PCR for detection of SARS-CoV-2 in nasopharyngeal swabs. Two hundred rapid antigen-positive nasopharyngeal swabs obtained from COVID-19 suspects/contacts/preoperative/ screening patients were subjected to RT-PCR to study the correlation with cycle threshold (CT) values obtained for all the antigen-positive cases. 200 Rapid COVID-19 LFA-positive samples were analysed in the present study. Amidst the LFA-positive samples included in the study 187 (93.5%) were found to have concordant results when subjected to the gold-standard Real-time PCR. Discordant results were documented in 13 (6.5%) COVID-19 LFA-positive samples which were found to be negative by RT-PCR. The average Cycle threshold values were found to be 23.75 for the E gene, 25.36 for the N gene and 24.07 for RdRp gene. The average PCR Cycle threshold of LFA positive cases remained significantly undeterred (p<0.5) throughout the time period of the study stipulating the undaunted viral load across the different waves of the pandemic. Maximum association of LFA positivity with symptom manifestation was seen during the 1st wave of COVID-19 (September-December 2020 in India). The association of symptoms with LFA test positivity reduced to a significant extent during the 3rd wave of the pandemic in January 2022 (p<0.5) indicating the reduced clinical severity but not infectivity of the SARS-CoV-2 infection during the 3rd wave of the pandemic. When compared to RT-PCR, lateral flow assay-based diagnostic techniques are more economically and technically convenient while maintaining a high degree of concordance. These tests offer a clear benefit in terms of expediting patient triage and, consequently, improving patient management. RT-PCR being highly sensitive assay can aid diagnosis in patients with low viral load and seems superior than the LFA which requires a higher vial load for positivity. Considering the above factors SARS-CoV-2 LFAs find utility as proxy infectivity indicating modalities for rapid triaging and patient management.